A Gold Nanocage/Cluster Hybrid Structure for Whole‐Body Multispectral Optoacoustic Tomography Imaging, EGFR Inhibitor Delivery, and Photothermal Therapy. Issue 33 (27th June 2019) - Zhan, Chenyue; Huang, Yong; Lin, Guifang; Huang, Shuailing; Zeng, Fang; Wu, Shuizhu
Abstract: Gold nanocages (AuNCs) and gold nanoclusters (AuClusters) are two classes of advantageous nanostructures with special optical properties, and many other attractive properties. Integrating them into one nanosystem may achieve greater and smarter performance. Herein, a hybrid gold nanostructure for fluorescent and optoacoustic tomography imaging, controlled release of drugs, and photothermal therapy (PTT) is demonstrated. For this nanodrug (EA–AB), an epidermal growth factor receptor (EGFR) inhibitor erlotinib (EB) is loaded into AuNCs, which are then capped and functionalized by biocompatible AuCluster@BSA (BSA = bovine serum albumin) conjugates via electrostatic interaction. Upon cell internalization, the lysosomal proteases and low pH cause the release of EB from EA–AB, and also induce fluorescence restoration of the AuCluster for imaging. Irradiation with near‐infrared light further promotes the drug release and affords a PTT effect as well. The AuNC‐based nanodrug is optoacoustically active, and its biodistribution and metabolic process have been successfully monitored by whole‐body and 3D multispectral optoacoustic tomography imaging. Owing to the combined actions of PTT and EGFR pathway blockage, EA–AB exhibits marked tumor inhibition efficacy in vivo. Abstract : A hybrid gold cage‐based nanodrug has been developed for tumor inhibition via epidermal growth factor receptor pathway blockage and photothermal therapy, which can release the active drug in acidic tumor environment and achieve tumor ablation upon light irradiation. The release of the drug and biodistribution of the nanostructure can be, respectively, visualized by fluorescence imaging and multispectral optoacoustic tomography imaging.